Bayesian correction of H(z) cosmic chronometers data with systematic errors - Kvint, N.R. [UNESP]; Jesus, J.F. [UNESP]; Pereira, S.H. [UNESP] (IOP Publishing, 2025)
We show that the 32 H(z) data from cosmic chronometers have overestimated uncertainties and we use a Bayesian method to correct and reduce it. Then we use the corrected data to constrain flat ΛCDM and OΛCDM parameters. For the flat ΛCDM model, we have as result H 0 = 67.1 ± 4.0 km s-1 Mpc-1 and Ω m = 0.333+0.041 -0.057. While for the OΛCDM model, we found H 0 = 67.2 ± 4.8 km s-1 Mpc-1, Ω m = 0.36 ± 0.16 and ΩΛ = 0.71+0.36 -0.28. These results goes from 22% up to 28% uncertainty reduction when compared to the constraints of the both uncorrected models.